2012
DOI: 10.1111/j.1600-0501.2012.02439.x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Ultrastructural study by backscattered electron imaging and elemental microanalysis of biomaterial‐to‐bone interface and mineral degradation of bovine xenografts in maxillary sinus floor elevation

Abstract: The biomaterial proved to be biocompatible and osteoconductive when used as a bone substitute for maxillary sinus elevation. The grafting material used is not a completely resorbable material over the time period covered by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Our study found that this type of graft was able to house the remaining bone particles by affixing a layer of immature bone tissue, with rare foci of inflammation. Despite some studies found in the literature reporting negative results using xenografts depending on the experimental conditions and type of graft (Levai et al 2003;Ledford et al 2013), others show its beneficial effects in healing (Astore et al 2005;Athanasiou et al 2010;Ram ırez-Fern andez et al 2013;Calasans-Maia et al 2014). Accordingly, our work observed in the histological analysis little remaining of this graft apposition of bone tissue, as well as the presence of resorption lacunae occupied by active osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that this type of graft was able to house the remaining bone particles by affixing a layer of immature bone tissue, with rare foci of inflammation. Despite some studies found in the literature reporting negative results using xenografts depending on the experimental conditions and type of graft (Levai et al 2003;Ledford et al 2013), others show its beneficial effects in healing (Astore et al 2005;Athanasiou et al 2010;Ram ırez-Fern andez et al 2013;Calasans-Maia et al 2014). Accordingly, our work observed in the histological analysis little remaining of this graft apposition of bone tissue, as well as the presence of resorption lacunae occupied by active osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common augmentation procedures is sinus lifting in the lateral maxilla. Many bone substitutes have been shown to be reliable, even without additional autogenic bone Heinemann et al, 2009a,b;Nevins et al, 2013;Ramírez-Fernández et al, 2013). To improve the condition for the implant placement, early augmentation directly after tooth extraction has been recommended, and different bone substitutes have been investigated in this context.…”
Section: Augmentation Materialsmentioning
confidence: 99%
“…However, the use of the allograft should be cautious, as transmission of pathogens may occur if safety measures are not undertaken (Frost, Fonseca, & Burkes Jr., 1982). Regarding the use of heterologous bone, some studies show negative results (Ledford, Nunley 2nd, Viens, & Lark, 2013;Levai, Bringer, Descamps, & Boisgard, 2003) and other studies show positive results (Astore, Ricci, Ursino, & Spotorno, 2005;Athanasiou et al, 2010;Calasans-Maia et al, 2014;Ramirez-Fernandez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%